Neuropathology of Early Sudden Infant Death Syndrome—Hypoplasia of the Pontine Kolliker-Fuse Nucleus: A Possible Marker of Unexpected Collapse during Skin-to-Skin Care - Lavezzi, Anna M.; Ferrero, Stefano; Paradiso, Beatrice; Chamitava, Liliya; Piscioli, Francesco; Pusiol, Teresa (American Journal of Perinatology, 2019)
Objective To find a possible pathogenetic mechanism of the early sudden infant death occurring in newborns during the skin-to-skin care (SSC), through the examination of neuronal centers regulating the vital activities.Study Design This is an in-depth examination of the brain stem in 22 healthy term newborns, suddenly died in the first hour of life without the identification of a cause at autopsy (early sudden infant death syndrome [eSIDS]), 12 of them concomitantly with SSC, and 10 with age-matched controls died of known pathology.Results Developmental alterations of neuronal structures of the brain stem were highlighted in 19 of the 22 eSIDS, but not in control. The hypoplasia of the pontine Kölliker-Fuse nucleus (KFN), an important respiratory center, was diagnosed at the histological examination, validated by morphometric quantifications, in 11 of the 12 eSIDS while they were placed on the mother's chest and in 2 of the 10 SSC unrelated neonatal deaths.Conclusion The delayed development of the KFN could represent a specific finding of eSIDS occurring during SSC. Therefore, it is necessary to point out that the SSC represents a further risk factor that must be added to others already known for sudden infant death syndrome. Then this practice needs appropriate monitoring strategies of the infant's conditions.
Keywords: skin-to-skin care; sudden unexpected postnatal collapse; sudden infant death syndrome; early sudden infant death syndrome; risk factors; neuropathology; brain stem; Kölliker-Fuse nucleus